"The Pictures Can Say More Things": Change Across Time in Young Children's References to Images and Words During Text Discussion. Issue 3 (28th March 2016) - Aukerman, Maren; Chambers Schuldt, Lorien
Abstract: Although scholarship in New Literacies increasingly emphasizes multimodal reading, some traditional perspectives on comprehension pedagogy continue to advocate for focusing discussion on linguistic content of texts, concerned that allowing students to discuss illustrations could siphon attention from the words (linguistic content). Largely absent from this debate has been close examination of how young students explicitly reference images versus linguistic content during text discussions where both are accepted as viable information sources, particularly studies considering whether such referencing might change across time. Our study analyzes nine discussion transcripts to examine second graders' explicit references to images and linguistic content during discussions across a school year. We asked three questions: (1) How did students' relative verbal emphasis on images versus linguistic content change? (2) Did the frequency of references to images and linguistic content differ between more and less proficient decoders? and (3) How did the teacher's language change across time, and were any changes related to changes observed in students? We found that students mostly referenced images early in the year. Across time, students shifted toward greater referencing of linguistic content, but less proficient decoders referenced linguistic content less frequently than more proficient decoders. These findings support an expanded conception of emergent literacy and of early literacy pedagogy that encompasses textual oracy practices—specifically, young students' talk with one another about multimodal dimensions of text.